2012
DOI: 10.2478/v10007-012-0031-0
|View full text |Cite
|
Sign up to set email alerts
|

Formulation development of an albendazole self-emulsifying drug delivery system (SEDDS) with enhanced systemic exposure / Razvoj samoemulzifirajućeg sustava za isporuku albendazola (SEDDS) s pojačanom sistemskom apsorpcijom

Abstract: Most of the new chemical entities (NCEs) are poorly water-soluble and pose a challenge to developing an optimum solid oral dosage form. Oral route has been the major route of drug delivery for the treatment of various diseases. Delivery of poorly water--soluble molecules by oral route is difficult because approximately 40 % of drug compounds are limited to low aqueous solubility, which leads to restricted oral bioavailability, high intra-and inter-subject variability and lack of dose proportionality (1).To inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
9
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(11 citation statements)
references
References 30 publications
2
9
0
Order By: Relevance
“…Thus, the overall stability of all SNEDDS formulae under these stress conditions was found to be acceptable. These results concur with Ashok et al, who prepared Albendazole self-emulsifying drug delivery system (SEDDS) and found that a sudden change in temperature had no effect in the entropy of the system [ 52 ].…”
Section: Resultssupporting
confidence: 90%
“…Thus, the overall stability of all SNEDDS formulae under these stress conditions was found to be acceptable. These results concur with Ashok et al, who prepared Albendazole self-emulsifying drug delivery system (SEDDS) and found that a sudden change in temperature had no effect in the entropy of the system [ 52 ].…”
Section: Resultssupporting
confidence: 90%
“…It is poorly soluble, with an aqueous solubility of 0.2 μg/mL at 25 °C, 1 μg/mL at pH 6.0, and a log p value of 3.5. It has weak basic properties (pK a1 = 2.68 and pK a2 = 11.83) [4,5]. Albendazole falls into the biopharmaceutical classification system (BCS) class II category with a high permeability and low solubility.…”
Section: Introductionmentioning
confidence: 99%
“…Because of its low aqueous solubility, it is poorly and erratically absorbed following oral administration. Following oral administration in rats, 20–30% is absorbed, and in humans, less than 5% is absorbed [1,2,4,6].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently the molecule has been successfully tested for anticancer properties against a wide range of cancers such as ovarian, breast, prostate and a number of other cancers in both in vitro and in vivo models 4-6. However, ABZ by virtue of its molecular structure is sparingly soluble in water (0.2µg/ml) although it is highly permeable through biological membranes 7. ABZ is quite soluble in organic solvents (log P = 3.5), however the inherent toxicity found in such solvents is a disadvantage 8, 9 when preparing for intravenous (IV) or intra-peritoneal (IP) formulations.…”
Section: Introductionmentioning
confidence: 99%